Adaptive Gamified Coding Learning Model to Increase Engagement and Computational Thinking Skills in Junior High - Budi Tri Cahyono; Suparmi; Enggar Jati Sasongko (Universitas Negeri Padang, 2026)
Computational thinking in the digital era encourages integrating coding education into junior high school curricula. This study examines the effectiveness of an adaptive gamified coding-based learning model in creating a more personalized and engaging learning experience. The model integrates adaptive strategies, gamification elements, and interactive challenges to enhance student motivation and participation. Using a quasi-experimental design, data were collected through engagement questionnaires and computational thinking tests. Results show an 87% improvement in computational thinking skills in the experimental group, compared to 13% in conventional learning. A positive relationship between engagement and computational thinking was also identified, indicating benefits for cognitive development and learning motivation. Additionally, a positive relationship was identified between student engagement and computational thinking ability. These results suggest that integrating adaptive learning and gamification effectively supports both cognitive development and learning motivation. This study contributes to advancing innovative learning models relevant to digital-era education